Evaluation of oral health promotion in the workplace: the effects on dental care costs and frequency of dental visits - Ide R, Mizoue T, Tsukiyama Y, Ikeda M, Yoshimura T (Blackwell Synergy, 2001)
An oral health promotion program has been conducted since 1989 at a shipyard in Japan.